Rubber-metal laminated gasket material
By using organic titanium compounds and aluminum oxide treated with titanium coupling agent as surface treatment agent layers in rubber-metal composite sealing materials, the problem of bonding and peeling of existing materials under high temperature and long-term LLC environment is solved, and the high temperature LLC heat resistance of the material is significantly improved.
Patent Information
- Application Number
- JP2024530873
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-27
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2043-06-27
AI Technical Summary
The existing rubber-metal composite sealing materials are difficult to maintain good bonding performance under high temperature and long-term LLC environments, resulting in bonding and peeling problems and affecting the normal operation of the engine.
The surface treatment agent layer, the adhesive layer and the rubber layer are sequentially coated on the metal plate. The surface treatment agent layer contains an organic titanium compound and aluminum oxide treated with a titanium coupling agent. The element mass ratio is 8:92 to 46:54 from titanium to aluminum. This structure improves the heat resistance of LLC.
Under high temperature conditions of 150°C, the material can maintain good LLC heat resistance within 300 hours, avoid adhesive peeling, and improve engine sealing performance.
Smart Images

Figure 0007667915000003 
Figure 0007667915000001 
Figure 0007667915000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber-metal laminate gasket material, and more particularly to a fluororubber-metal laminate gasket material suitable for use as an engine cylinder head gasket or the like. [Background technology]
[0002] As metal materials for engine cylinder head gaskets, which require water resistance, LLC (long life coolant) resistance, and heat resistance, mild steel and stainless steel are mainly used, but when a vulcanizing adhesive is directly applied to these and they are bonded to rubber, the liquid-resistant adhesive durability is poor, and when this rubber-metal laminate is subjected to an immersion test in which it is immersed in water, LLC, etc., the adhesive peels off. If the rubber peels off inside the engine due to poor LLC resistance, it can lead to engine failure.
[0003] To improve the adhesion between metal sheets and rubber, methods of treating the surface of stainless steel sheets, such as zinc phosphate treatment and iron phosphate treatment, are used. These methods involve immersing a degreased steel sheet in an acidic chemical solution to form an insoluble coating on the steel sheet, which prevents rust and ensures adhesion to adhesives. However, there are problems with this method, such as the generation of sludge (industrial waste) at the coating formation stage and the need to constantly add chemicals because the chemical components are reduced by reaction, resulting in high costs.
[0004] The present applicant has previously proposed to apply a paint-type chromate treatment to the surface of a stainless steel sheet as a pretreatment before applying a vulcanizing adhesive, thereby improving resistance to water, LLC, etc. (Patent Documents 1 and 2). However, in the paint-type chromate treatment, Cr 6+ Since it contains ions, it is not preferable from an environmental perspective.
[0005] Furthermore, as a method that does not use zinc phosphate, iron phosphate, chromium, etc., a surface treatment agent containing organic resin, silica, titanium derived from fluoride, and zirconia has been proposed. However, since the agent contains fluorine, it is necessary to remove the fluorine from the wastewater, which results in a complex facility (see Patent Document 3).
[0006] On the other hand, fluorine-free treatment agents have been proposed as improvements on the above-mentioned surface treatment agents, but they do not provide sufficient adhesion when used in harsh environments such as cylinder head gaskets exposed to high-temperature LLC vapor (Patent Document 4).
[0007] In response to this problem, the applicant has disclosed in Patent Document 5 that in a rubber-metal laminated gasket material obtained by successively laminating a surface treatment agent layer, an adhesive layer, and a rubber layer on a metal plate, the surface treatment agent layer does not contain chromium and has a mixture ratio of 20 to 90% by weight of a fluorine-free titanium compound and 10 to 80% by weight of alumina, and the surface treatment agent has a content of 1 to 20% by weight as metallic titanium, and is applied in an amount of 30 to 1,000 mg / m on one side. 2 The paper proposes a rubber-metal laminate gasket material that contains neither chromium nor fluorine and has excellent LLC resistance under high temperature conditions, which is formed by applying a coating such that the coating is applied so as to form a rubber-metal laminate gasket. Patent documents 6 to 7 also propose combining an organometallic compound containing a chelate structure with an inorganic filler such as alumina or silica as a primer for the rubber-metal laminate gasket. However, further improvement is required in terms of LLC resistance under high temperature conditions for long periods of time. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2000-006307 A [Patent Document 2] Japanese Patent Application Publication No. 11-221875 [Patent Document 3] Patent No. 5,050,316 [Patent Document 4] WO 2011 / 002040 [Patent Document 5] WO 2014 / 208113 [Patent Document 6] JP 2005-180682 A [Patent Document 7] JP 2006-218629 A [Patent Document 8] Japanese Patent Application Publication No. 7-165953 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a rubber-metal laminate gasket material that has excellent LLC resistance under high temperature conditions. [Means for solving the problem]
[0010] The object of the present invention is to provide a rubber-metal laminated gasket material having a surface treatment agent layer, an adhesive layer, and a rubber layer laminated in this order on a metal plate, the surface treatment agent layer containing an organic titanium compound and alumina treated with a titanium coupling agent, and the element mass ratio of titanium and aluminum in the surface treatment agent film is 8:92~46:54 This is achieved by a rubber-metal laminate gasket material formed using a surface treatment agent that is Effect of the Invention
[0011] The rubber-metal laminate gasket material according to the present invention has the effect of not causing adhesion peeling even in a heat resistance test method in LLC that takes into account the actual usage environment of an engine cylinder head gasket, and exhibiting excellent LLC resistance even under high temperature conditions such as 150°C for 300 hours. Specifically, in a combination of an organometallic compound and an inorganic filler, the LLC resistance of the primer is improved by treating the alumina surface with a coupling agent, and the improved LLC adhesion resistance prevents the rubber of the gasket from peeling off inside the engine, leading to the improvement of problems.
[0012] In addition, the surface treatment agent contains neither chromium nor fluorine, which is preferable from an environmental perspective, and because it is fluorine-free, there is no need to remove fluorine from wastewater.Furthermore, the surface treatment does not form a film through a chemical reaction with the stainless steel sheet as in zinc phosphate treatment, but is formed by simply applying a prepared agent, so there is also the excellent effect of no generation of sludge. [Brief description of the drawings]
[0013] [Figure 1] FIG. 13 is a diagram showing the evaluation scores of the peeling state after the drawing test carried out in the examples and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] As the metal plate, a mild steel plate, a stainless steel plate, an aluminum plate, an aluminum die-cast plate, etc. are used. As the stainless steel plate, SUS301, SUS301H, SUS304, SUS430, etc. are used. Since the plate is used for gaskets, the plate thickness is generally about 0.1 to 2 mm. On these metal plates, a surface treatment agent containing an organic titanium compound and alumina surface-treated with a titanium coupling agent is applied. In this case, the metal plate is preferably used after roughening treatment and alkali degreasing treatment.
[0015] The surface treatment agent has an element mass ratio of titanium and aluminum in the surface treatment agent film. 8:92~46:54 If the element mass ratio is other than this ratio, peeling occurs in the part exposed to LLC vapor after immersion in LLC at 150°C for 300 hours, as shown in the comparative example described later.
[0016] Examples of the organic titanium compound include alkoxytitanium compounds, titanium acylates, and titanium chelates containing a Ti-O-C bond formed by Ti(IV) or Ti(III) and a compound having an alcoholic hydroxyl group, a phenolic hydroxyl group, or a carboxyl group. Examples of the organic titanium compound include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetraoctyl titanate, and compounds represented by the general formula: TIFF0007667915000001.tif37166TIFF0007667915000002.tif40166R:CH3, C2H5, n-C3H7, i-C3H7, n-C4H9, i-C4H9, etc. Lower alkyl group having 1 to 5 carbon atoms n: an integer between 1 and 4 The organic titanium compounds are composed of a chelate ring represented by the formula (I) and an alkoxy group, specifically, isopropoxytitanium bis(ethylacetoacetate), 1,3-propanedioxytitanium bis(ethylacetoacetate), diisopropoxytitanium bis(acetylacetonate), titanium tetra(acetylacetonate), etc. These are commercially available products, such as Mitsubishi Gas Chemical's tetra n-butyl titanate, Matsumoto Fine Chemical's Orgatics TA-10, Orgatics TA-21, Orgatics TA-23, Orgatics TA-30, Orgatics TC-100, etc., which can be used as they are.
[0017] The titanium coupling agent surface-treated alumina is one in which the surface of the alumina is treated with a titanium coupling agent. In practice, a commercially available product, such as Matsumoto Fine Chemical's product TC-500 (titanium diethanol aminate), can be used as is. The particle size of the alumina used is not particularly limited. By carrying out such surface treatment, the functional groups on the alumina surface are reduced, the reaction between the alumina and the organometallic compound is suppressed, and the reaction points between the organometallic compound and the metal steel sheet can be increased. Here, if alumina that has not been surface-treated is used, the functional groups on the alumina surface react with the organometallic compound, inhibiting the adhesion between the organometallic compound and the stainless steel sheet. On the other hand, if alumina is not used, the liquid shielding property of the primer is reduced, and when the engine block / head made of aluminum comes into contact with water or LLC, an electric potential is generated between the stainless steel sheet of the CHG, promoting peeling.
[0018] The above components are essential, and the surface treatment agent is prepared by mixing these components and dissolving or dispersing them in a solvent. The surface treatment agent is applied to both surfaces of a metal sheet at a concentration of 30 to 2500 mg / m by immersion, spraying, brush printing, roll coating, or other methods. 2 , preferably 500 to 1500 mg / m 2 The coating is applied to one side in an amount (weight per unit area) of 100 to 250°C, dried at room temperature or with hot air, and then baked for 1 to 20 minutes at 100 to 250°C. If the coating amount is more than this, peeling will occur at the parts immersed in the LLC liquid, while if the coating amount is less than this, the adhesion between the metal and the rubber will decrease. The solvent for dissolving and dispersing the organotitanium compound and the titanium coupling-treated alumina is not particularly limited, but for example, methanol or the like is used.
[0019] On the surface treatment agent layer applied to the metal plate and dried, a resin-based vulcanizing adhesive such as a thermosetting phenolic resin or an epoxy resin is applied as a rubber adhesive. As the thermosetting phenolic resin, any thermosetting phenolic resin such as cresol novolac type phenolic resin, cresol resol type phenolic resin, or alkyl modified type phenolic resin can be used. As the epoxy resin, a cresol novolac type epoxy resin is preferably used, in which case a bisphenol novolac type phenolic resin is used as a curing agent, and an imidazole compound is used as a curing catalyst, and for example, an epoxy resin-based vulcanizing adhesive in which an epoxy resin and an imidazole curing agent are mixed in a ratio of 9.5:0.5 to 7:3 is used.
[0020] These resin-based vulcanizing adhesives are generally prepared as organic solvent solutions with component concentrations of about 1 to 5% by weight using alcohol-based organic solvents such as methanol, ethanol, isopropanol, etc., or ketone-based organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc., either alone or in combination. They are applied in the same manner as for surface treatment agents, with a coating density of 100 to 2,500 mg / m 2 After drying at room temperature or with hot air, it is baked at 100 to 250°C for 1 to 20 minutes.
[0021] On the vulcanized adhesive layer thus formed, an unvulcanized rubber compound is applied as an organic solvent solution of the rubber compound so as to form a vulcanized layer with a thickness of about 5 to 120 μm on both sides. The rubber compound is prepared by kneading using a kneader such as an intermix, kneader, or Banbury mixer, or an open roll, and is prepared as a rubber paste coating liquid so that the solid content concentration is about 20 to 50% by weight. As the rubber, fluororubber, nitrile rubber, etc. are used, and fluororubber is preferably used.
[0022] As the fluororubber, either a polyol vulcanizable or peroxide vulcanizable fluororubber can be used.
[0023] Examples of polyol-vulcanizable fluororubbers generally include copolymers of vinylidene fluoride with at least one of other fluorine-containing olefins, such as hexafluoropropene, pentafluoropropene, tetrafluoroethylene, trifluorochloroethylene, vinyl fluoride, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), and copolymers of these fluorine-containing olefins with propylene, and the like. These fluororubbers are polyol-vulcanized with a polyhydroxy aromatic compound, such as 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)perfluoropropane, or hydroquinone.
[0024] Also, the peroxide vulcanizable fluororubber may be, for example, a fluororubber having iodine and / or bromine in the molecule, and these fluororubbers are generally vulcanized (crosslinked) by an organic peroxide used in peroxide vulcanization. In this case, it is preferable to use a polyfunctional unsaturated compound, typically triallyl isocyanurate, in combination with the organic peroxide.
[0025] As the unvulcanized fluororubber compound, for example, the following compounding example is shown. (Combination example I) Polyol vulcanizable fluororubber (DuPont Viton A500) 100 parts by weight MT Carbon Black 60 〃 Silica (Toso Silica Product NIPSIL LP) 5 Same Calcium hydroxide (Omi Chemical Industry Product CALDIC2000) 2 Same Magnesium oxide (Kyowa Chemical Industry Co., Ltd. Kyowamag 150) 5 Same Processing aid (TECHNICAL PROCESSING product TE-58A) 0.5 〃 Vulcanizing agent (DuPont Curative #30) 8 Same Vulcanization accelerator (company product Curative #20) 4 Same (Combination example II) Polyol vulcanizable fluororubber (DuPont product Viton E45) 100 parts by weight Calcium metasilicate 40% MT Carbon Black 20 〃 Magnesium oxide (Kyowa Chemical Products Magnesia #150) 6 Same Calcium hydroxide 3 〃 Vulcanizing agent (Curative #30) 2 Same Vulcanization accelerator (Curative #20) 1 〃 (Combination example III) Polyol vulcanizable fluororubber (DuPont product Viton E60C) 100 parts by weight Vulcanizing agent (DuPont Diac No.3) 3 Same Magnesium oxide (Kyowa Chemical Products Magnesia #30) 10 〃 MT Carbon Black 30 〃 (Combination example IV) Peroxide cross-linked fluororubber (Daikin product Daiel G901) 100 parts by weight Calcium metasilicate 20% MT Carbon Black 20 〃 Magnesium oxide (magnesia #150) 6 〃 Calcium hydroxide 3 〃 Triallyl isocyanurate 1.8 〃 Organic peroxide (Nippon Oil Products Perhexa 25B) 0.8 Same
[0026] Nitrile rubber (NBR) can be used as a compound using a sulfur-based vulcanizing agent such as sulfur, tetramethylthiuram monosulfide, or tetramethylthiuram disulfide, but is preferably used as an unvulcanized nitrile rubber compound using an organic peroxide as a crosslinking agent. For example, the following compounding example is shown as an example of such a peroxide crosslinking system unvulcanized nitrile rubber compound.
[0027] (Combination example V) NBR (JSR product N235S) 100 parts by weight SRF Carbon Black 80 〃 Calcium carbonate 80% Powdered silica 20 〃 Zinc oxide 5 〃 Anti-aging agent (Ouchi Shinko Chemical Products Nocrac 224) 2 Same Triallyl isocyanurate 2 Same 1,3-Bis(tert-butylperoxy)isopropylbenzene 2.5 〃 Plasticizer (Bayer's product Bucanol OT) 5 Same (Formulation example VI) NBR (medium-high nitrile; JSR product N237) 100 parts by weight HAF Carbon Black 80 〃 Powdered silica 60 〃 Zinc oxide 5 〃 Stearic acid 1 〃 Anti-aging agent (Ouchi Shinko Chemical Products ODA-NS) 1 Same Organic peroxide (Perhexa 25B) 6 〃 N,Nm-Phenylenedimaleimide 1 〃
[0028] The applied unvulcanized rubber layer is dried at room temperature to about 100°C for about 1 to 15 minutes, and the organic solvents, such as alcohols such as methanol and ethanol, ketones such as methyl ethyl ketone and methyl isobutyl ketone, aromatic hydrocarbons such as toluene and xylene, or mixed solvents thereof, are evaporated, and then the layer is heated and vulcanized at about 150 to 230°C for about 0.5 to 30 minutes, and may be pressurized for vulcanization as necessary. In terms of use as a gasket, the vulcanized rubber layer is preferably, for example, 80 or more in hardness (durometer A) and 50% or less in compression set (100°C, 22 hours), and is not particularly limited by the composition as long as it satisfies the desired properties. In addition, if anti-adhesion is required, an anti-adhesion agent may be applied to the surface.
[0029] Anti-adhesive agents are used for the purpose of preventing adhesion between rubbers or between rubber and metal. Any agent can be used as long as it can form a coating on the vulcanized rubber layer. Examples of such agents include silicone-based, fluorine-based, graphite-based, amide, paraffin or other wax-based, polyolefin-based or polybutadiene-based agents. Preferably, an anti-adhesive agent is used that consists of a liquid 1,2-polybutadiene hydroxyl group-containing material, a 1,2-polybutadiene isocyanate group-containing material, and an organic solvent dispersion of a polyolefin resin, such as a rubber cement coating liquid in which wax and graphite are dispersed in a ratio of 9:1 to 5:5 (Patent Document 8). EXAMPLES
[0030] The present invention will now be described in detail with reference to examples. However, the present invention, including its effects, is not limited to these examples.
[0031] Example 1 A surface treatment agent was applied to an alkaline-degreased SUS301 stainless steel plate (thickness 0.2 mm) using titanium acetylacetonate (Matsumoto Fine Chemical's product Orgatics TC-100; (i-C3H7O)2Ti(C6H9O3)2) and titanium coupling agent-treated alumina (Matsumoto Fine Chemical's product Orgatics TC-500) so that the element mass ratios of Ti and Al in the surface treatment agent film were 8% by weight and 92% by weight, respectively, at a coating weight of 700 mg / m on one side. 2 The mixture was then baked at 200°C for 10 minutes to form a primer layer.
[0032] On the steel plate coated with this surface treatment agent, an epoxy resin-based vulcanizing adhesive made by mixing epoxy resin (YDCN-700-7, a product of Nippon Steel Chemical & Material) and imidazole hardener (Curesol 2E4MZ-CN, a product of Shikoku Kasei) in a ratio of 8:2 was applied at a film weight of 300 mg / m. 2 After drying in air, the coating was subjected to a baking treatment at 200° C. for 5 minutes.
[0033] A 25% by weight solution of the fluororubber compound of Formulation Example I in a mixed solvent of methyl isobutyl ketone and methanol (weight ratio 8:2) was applied onto this vulcanized adhesive-coated steel plate and dried at 60°C for 15 minutes to form an unvulcanized rubber layer 20 μm thick on one side, which was then vulcanized at 200°C for 5 minutes. A rubber paste coating liquid in which wax (Mitsui Chemicals product 4202E) and graphite (Oriental Industries product AT-No. 40) were dispersed in a ratio of 8:2 was then applied and baked at 200°C for 5 minutes to form an anti-adhesion layer, producing a fluororubber-metal laminated gasket material.
[0034] Example 2 In Example 1, titanium acetylacetonate- and titanium coupling agent-treated alumina were used in which the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 23 wt % and 77 wt %, respectively.
[0035] Example 3 In Example 1, titanium acetylacetonate- and titanium coupling agent-treated alumina were used, in which the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 46 wt % and 54 wt %, respectively.
[0036] Example 4 In Example 1, tetraoctyl titanate (Matsumoto Fine Chemical product Orgatics TA-30; Ti[OCH2CH(C2H5)C4H9]4) was used instead of titanium acetylacetonate, and tetraoctyl titanate and titanium coupling agent-treated alumina was used in which the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 33% by weight and 67% by weight, respectively.
[0037] Comparative Example 1 In Example 1, untreated alumina (Denka product ASFP-20) was used instead of the titanium coupling agent-treated alumina, and titanium acetylacetonate and alumina were used in which the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 17% by weight and 83% by weight, respectively.
[0038] Comparative Example 2 In Example 1, titanium acetylacetonate- and titanium coupling agent-treated alumina were used in which the element mass ratios of Ti and Al in the surface treatment agent film were adjusted to 72 wt % and 28 wt %, respectively.
[0039] Comparative Example 3 In Example 1, titanium acetylacetonate was not used, and alumina treated with a titanium coupling agent in which the element mass ratio of Al in the surface treatment agent film was 100% by weight was used.
[0040] Comparative Example 4 In Example 1, a silane coupling agent (Toray Dow Corning product Z6011) was used instead of titanium acetylacetonate, and the alumina treated with the silane coupling agent and titanium coupling agent was used such that the element mass ratios of Si and Al in the surface treatment agent film were adjusted to 25% by weight and 65% by weight, respectively.
[0041] The rubber-metal laminate gasket materials obtained in the above respective Examples and Comparative Examples were evaluated for adhesiveness under high-temperature LLC conditions. Adhesion evaluation: In a pressure vessel, the rubber-metal laminated gasket material is The lower half of the product is immersed in immersion liquid (LLC (Toyota Long Life Liquid) Immerse in a 50:50 mixture of grease and water at 150°C. Leave it for 300 hours, then immerse it in an immersion liquid according to JIS K6894. The lower immersion area and the upper part of the immersion liquid are exposed to LLC vapor. The upper exposed part (unimmersed part) was plotted in a drawing test. Rated 1 like A score of 4 or more was considered a pass.
[0042] The results obtained are shown in the following table. table Material Part Fruit 1 Fruit 2 Fruit 3 Real 4 ratio 1 ratio 2 ratio 3 ratio 4 LLC immersion section 5 5 5 5 5 5 5 5 LLC vapor exposure section 5 5 5 5 1 1 1 1
[0043] From the above results, the following can be concluded: (1) In each embodiment, a rubber-metal laminate gasket material having excellent LLC resistance under high temperature conditions was obtained. (2) When the surface treatment agent used contained an organic titanium compound and a titanium coupling agent-treated alumina outside the specified amount range, the adhesion was low in the upper exposed portion (unimmersed portion) exposed to LLC vapor above the LLC immersion liquid, and the gasket could not withstand use in the actual operating environment of an engine cylinder head gasket (Comparative Examples 1 to 2). (3) When alumina that has not been surface-treated with a titanium coupling agent is used, the functional groups on the alumina surface react with the organometallic compound, inhibiting adhesion between the organometallic compound and the stainless steel sheet, resulting in low adhesion in the upper exposed area (unimmersed area) exposed to LLC vapor above the LLC immersion solution (Comparative Example 3). [Industrial Applicability]
[0044] The rubber-metal laminate gasket material according to the present invention has excellent LLC resistance under high temperature conditions and is therefore effectively used as an engine cylinder head gasket, etc.
Claims
1. A rubber-metal laminated gasket material comprising a metal plate on which a surface treatment agent layer, an adhesive layer, and a rubber layer are laminated in that order, the surface treatment agent layer containing an organic titanium compound and alumina treated with a titanium coupling agent, and formed using a surface treatment agent in which the elemental mass ratio of titanium to aluminum in the surface treatment agent film is 8:92 to 46:
54.
2. 2. The rubber-metal laminate gasket material according to claim 1, wherein the organotitanium compound is an alkoxytitanium compound or a titanium chelate.
3. 2. The rubber-metal laminate gasket material according to claim 1, wherein the organotitanium compound is tetraoctyl titanate or titanium acetylacetonate.
4. 2. The rubber-metal laminate gasket material according to claim 1, wherein the adhesive is an epoxy resin adhesive.
5. 2. The rubber-metal laminate gasket material according to claim 1, wherein the rubber is a fluororubber.
6. 2. A rubber-metal laminate gasket material according to claim 1, further comprising an anti-tack agent layer formed on the rubber layer.
7. 2. The rubber-metal laminate gasket material according to claim 1, which is used as a gasket for an engine cylinder head.
8. 8. An engine cylinder head gasket manufactured from the rubber-metal laminate gasket material according to claim 7.
Citation Information
Patent Citations
Maleic continuous dehydrating method and apparatus
JP1975050316A
Surface treating agent for cured rubber
JP1995165953A
Rubber laminated metal panel
JP1999221875A
Rubber laminated metal panel
JP2000006307A
Nitrile rubber-metal laminated gasket material
JP2005180682A